Perspectives of primary health care staff on the implementation of a sexual health quality improvement program: a qualitative study in remote aboriginal communities in Australia - Belinda Hengel; Stephen Bell; Linda Garton; James Ward; Alice Rumbold; Debbie Taylor-Thomson; Bronwyn Silver; Skye McGregor; Amalie Dyda; Janet Knox; Rebecca Guy; Lisa Maher; et al. (BMC, 2018)
Abstract Background Young people living in remote Australian Aboriginal communities experience high rates of sexually transmissible infections (STIs). STRIVE (STIs in Remote communities, ImproVed and Enhanced primary care) was a cluster randomised control trial of a sexual health continuous quality improvement (CQI) program. As part of the trial, qualitative research was conducted to explore staff perceptions of the CQI components, their normalisation and integration into routine practice, and the factors which influenced these processes. Methods In-depth semi-structured interviews were conducted with 41 clinical staff at 22 remote community clinics during 2011-2013. Normalisation process theory was used to frame the analysis of interview data and to provide insights into enablers and barriers to the integration and normalisation of the CQI program and its six specific components. Results Of the CQI components, participants reported that the clinical data reports had the highest degree of integration and normalisation. Action plan setting, the Systems Assessment Tool, and the STRIVE coordinator role, were perceived as adding value to the program, but were less readily integrated or normalised. The remaining two components (dedicated funding for health promotion and service incentive payments) were seen as least relevant. Our analysis also highlighted factors which enabled greater integration of the CQI components. These included familiarity with CQI tools, increased accountability of health centre staff and the translation of the CQI program into guideline-driven care. The analysis also identified barriers, including high staff turnover, limited time involved in the program and competing clinical demands and programs. Conclusions Across all of the CQI components, the clinical data reports had the highest degree of integration and normalisation. The action plans, systems assessment tool and the STRIVE coordinator role all complemented the data reports and allowed these components to be translated directly into clinical activity. To ensure their uptake, CQI programs must acknowledge local clinical guidelines, be compatible with translation into clinical activity and have managerial support. Sexual health CQI needs to align with other CQI activities, engage staff and promote accountability through the provision of clinic specific data and regular face-to-face meetings. Trial registration Australian and New Zealand Clinical Trials Registry ACTRN12610000358044. Registered 6/05/2010. Prospectively Registered.